2016
DOI: 10.1016/j.jmbbm.2016.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Frequency-modulated atomic force microscopy localises viscoelastic remodelling in the ageing sheep aorta

Abstract: Age-related aortic stiffening is associated with cardiovascular diseases such as heart failure. The mechanical functions of the main structural components of the aorta, such as collagen and elastin, are determined in part by their organisation at the micrometer length scale. With age and disease both components undergo aberrant remodelling, hence, there is a need for accurate characterisation of the biomechanical properties at this length scale. In this study we used a frequency-modulated atomic force microsco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 28 publications
2
13
0
Order By: Relevance
“…By presenting both uniaxial and nanoindentation data we are able to compare our data with other studies and also correlate our novel nanoindentation method with more conventional, established mechanical testing methods. We believe that these data will serve as a useful reference given the increase in use of indentation-based techniques for aortic biomechanical analysis [29][30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…By presenting both uniaxial and nanoindentation data we are able to compare our data with other studies and also correlate our novel nanoindentation method with more conventional, established mechanical testing methods. We believe that these data will serve as a useful reference given the increase in use of indentation-based techniques for aortic biomechanical analysis [29][30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…A simple indentation experiment was carried out to determine the elastic moduli of samples. Some attempts were made to obtain both the storage and loss moduli of biological samples by superimposing the oscillating motion on the probe while indenting the samples [113,115,119]. For the clinical applications of AFM techniques, there have been an increasing number of studies investigating tissues obtained from a minimally invasive surgical intervention such as biopsy [47,50,120].…”
Section: Mechanical Compliancementioning
confidence: 99%
“…Mechanical stiffening has also been noted as a hallmark of cardiovascular complications [119,121]. A recent AFM study directly observed a significant increase in the elastic moduli of ventricular tissues freshly harvested from mice with pressure overloadinduced cardiac hypertrophy [121].…”
Section: Mechanical Compliancementioning
confidence: 99%
See 1 more Smart Citation
“…For example, age-related arterial stiffening is largely attributed to changes in the intima due to atherosclerosis, and degeneration of the media [4] . Furthermore, within these layers, alterations can be localized to individual components at the nano- and micro- scale [5] , [6] . Hence, to understand the mechanisms driving arterial stiffening, the nano-structure and mechanical properties of individual layers within the artery need to be considered.…”
Section: Introductionmentioning
confidence: 99%